Model Pengelolaan Harta Warisan Lahan Pertanian Dalam Perspektif Fikih Muamalah - Muhammad Zuhirsyan (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2021)
This study aims to determine the form of application of Islamic Agricultural Land Inheritance Management in Muamalah Economic Fiqh Perspective. The research model of this research is qualitative, with a muamalah fiqh approach. The method of extracting data in this study was carried out by interviewing and observing the Muslim community of the Simalungun Batak Tribe in Tebing Tinggi District, Serdang Bedagai Regency, North Sumatra. The application of this management is analyzed using the customary inheritance system law, which refers to Pancasila. The results showed that the management of land derived from cultural heritage objects can be carried out in the form of Muzar'ah, Mukhabarah and Musaqah and in accordance withthe principles of customary law in Indonesia.Keywords: Management, Assets, Inheritance, Agriculture, fiqh, Muamalah